Association of Physical Function and Physical Activity in Women with Rheumatoid Arthritis - Piva, Sara R (2010)
OBJECTIVE: The purpose of this study was to explore the associations between measures of physical activity (PA) and measures of physical function (PF) in women with rheumatoid arthritis (RA). We hypothesized that the strength of the associations between PA and PF would be moderate, and that after controlling for social and biomedical characteristics, the associations would decrease. METHODS: Forty seven women with RA participated in the cross-sectional analysis of this study (age 58 ± 6 years). Social and biomedical characteristics explored included age, ethnicity, disease duration, marital and educational status, height, weight, comorbidity, and disease activity. PF was measured by the self-reported Health Assessment Questionnaire (HAQ) and by a battery of performance-based measures that included the self-selected gait speed, the 5-chair rise test, and the single leg stance test. PA was measured by a portable activity monitor worn for 10 days, and was characterized in 2 ways: daily average number of steps, and daily energy expenditure during moderate levels of PA. RESULTS: Correlations between measures of PA and PF were small to moderate (zero-order correlations= .189 to .479). After controlling for social and biomedical characteristics, the correlations became smaller (semi-partial correlations= .095 to .277), and only HAQ remained significantly associated with PA. CONCLUSIONS: Associations between measures of PA and measures of PF are explained, in part, by social and biomedical characteristics in women with RA. The results indicate that measures of PF and PA may represent different constructs and support the need to measure PA in rehabilitation research in RA.